Proceedings of 1st International E-Conference on Energies 2014
DOI: 10.3390/ece-1-c003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Biodiesel from Karanja Oil by Using Silica Gel Reactor

Abstract: The oil extraction and biodiesel preparation from Karanja oil have different available methods namely acid catalyzed trans-esterification, acid catalyzed two-step and three-step method etc. The available methods are studied for biodiesel preparation from Karanja oil. The biodiesel conversion by esterification reaction may contain some moisture which may causes to slowdown the reaction rate and affects on the quality of biodiesel by making emulsion. The adsorption technique by using powder form of silica gal ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is a liquid fuel generated from biological resources and a renewable source of energy [3,4]. Different types of biodiesels are available (depending upon the source that they are extracted from) such as: bioethanol [5], karanja [6], jatropha [7], castor [8], sunflower and mustard [9] etc. According to the United State Energy Information Administration (USIA), biodiesel can serve as a substitute for petroleum-derived gasoline and diesel or distillate fuel [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is a liquid fuel generated from biological resources and a renewable source of energy [3,4]. Different types of biodiesels are available (depending upon the source that they are extracted from) such as: bioethanol [5], karanja [6], jatropha [7], castor [8], sunflower and mustard [9] etc. According to the United State Energy Information Administration (USIA), biodiesel can serve as a substitute for petroleum-derived gasoline and diesel or distillate fuel [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a fuel that has 20% biodiesel will be denoted by B20. When comparing biodiesel to petroleum-based diesel fuel, it is clearly evident that biodiesel is a lot more environmentally friendly [17][18][19][20][21][22]. A study sponsored by the United States Department of Agriculture and Department of Energy revealed that "Biodiesel yields 3.2 units of fuel product energy for every unit of fossil energy consumed in its life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…This is a challenge to fuel vehicles especially with high blends of biodiesel because biodiesel tends to gel (freeze) at higher temperatures than the conventional diesel. Compared to petro-diesel, biodiesel tends to have a much narrower range of temperatures between the cloud point (CP) and the pour point (PP) [120]. While there may be a 20-degree difference between the CP and the PP of petroleum diesel, biodiesel may have a difference of only a few degrees.…”
Section: Impact Of Cold Flow Properties On Engine Performancementioning
confidence: 99%